Integration of Geochemical and Geophysical Data for Downhole Rock Mass Characterisation - Kitzig, Maria Cornelia (Curtin University, 2018)
Exploration for mineral deposits is more challenging today as the target depth for new discoveries is increasing. New measuring and sensing technologies that enable real-time data acquisition are being developed to overcome these challenges. This study investigates how a joint, real-time analysis of these data-streams can add knowledge about the characteristics of a mineral deposit and complement an effective exploration strategy in the future.